Diastereoselective synthesis of highly substituted cyclohexanones and tetrahydrochromene-4-ones via conjugate addition of curcumins to arylidenemalonates - Nair, Deepa; Tiwari, Abhishek; Laha, Banamali; Namboothiri, Irishi N. N. (Beilstein Journal of Organic Chemistry, 2024)
A cascade inter–intramolecular double Michael strategy for the synthesis of highly functionalized cyclohexanones from curcumins and arylidenemalonates is reported. This strategy works in the presence of aqueous KOH using TBAB as a suitable phase transfer catalyst at room temperature. The functionalized cyclohexanones are formed as major products in moderate to excellent yields with complete diastereoselectivity in most cases. A triple Michael adduct, tetrahydrochromen-4-one, is also formed as a side product in a few cases with excellent diastereoselectivity.
Keywords: arylidenemalonates; curcumins; cyclohexanones; diastereoselective synthesis; Michael reaction; tetrahydrochromenones